New Directions in Geometric and Applied Knot Theory - Blatt, Simon (De Gruyter, 2018)
The aim of this book is to present recent results in both theoretical and applied knot theory&#8212which are at the same time stimulating for leading researchers in the &#64257eld as well as accessible to non-experts. The book comprises recent research results while covering a wide range of di&#64256erent sub-disciplines, such as the young &#64257eld of geometric knot theory, combinatorial knot theory, as well as applications in microbiology and theoretical physics.